Implementasi Media Sosial Instagram Sebagai Strategi Promosi Bagi Pengembangan Pemasaran Wisata New Sekipan KPH Surakarta Di Tawangmangu - Maitri, Acintya Anugrahana; Ridanasti, Erlita (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study was conducted to examine the implementation of the use of Instagram social media as a promotional strategy in the current digitalization era. This study aims to explore the implementation of the use of Instagram social media utilisation as a promotional strategy in an effort to increase the visibility and sales of products or services. In today's digital era, Instagram has become one of the most popular and effective platforms for marketing and promotional activities. Through a qualitative approach, this study collects data from various businesses that actively use Instagram for promotion, and analysed the strategies and results achieved. This research method uses a descriptive analysis approach as a qualitative method to understand and describe the use of social media as a marketing medium. Marketing activities in this case are the use of Instagram social media as a medium to introduce tourist attractions to reach the wider market. With the right promotion strategy, Instagram can be a very effective tool to attract customers' attention and build brand awareness. Focusing on content quality, audience engagement, and maximum use of Instagram features will help businesses achieve their marketing goals and grow their business better.